Penggunaan Bahasa Indonesia sebagai Bahasa Sehari-hari oleh Migran di Provinsi DKI Jakarta Berdasarkan Data Sensus Penduduk 1971 - Suyanto Suyanto (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2018)
This research is a linguistic demographic research. The focus of this study is the use of Indonesian (BI) by migrants as a colloquial language in the Province of the Special Capital Region of Jakarta based on 1971 Population Census data. This study aims: (1) to explain the number of Indonesian speakers nationally and according to ethnicity in Jakarta Province and (2) explaining the composition of migrants in Jakarta based on daily language or mother tongue. The data collection of this study uses the referral method that was developed with the technique of noting and analyzing data using descriptive statistical analysis. The results showed that the population of Indonesia was dominated by speakers of Javanese and Sundanese languages which were 40.44 percent and 15.06 percent respectively, and only 11.93 percent were Indonesian's mother tongue. The majority of migrants in Jakarta mostly use Indonesian for daily communication, which reaches 84.68 percent, and Javanese is used by 7.54 percent and third place in Sundanese is used by 3.96 percent. This conditions is far below the number of Javanese-speaking migrants who reached 41 percent and 31 percent of Sundanese. The occurrence of these symptoms is caused by: (1) the demands of work, (2) living with multilingual migrants, and (3) linguistic prestige.